(untitled) (Research, Society and Development, 2025)
Considering that special education is a field that challenges traditional teaching practices, the objective of this article was to analyze the policies, pedagogical practices, and challenges faced by this area in the contemporary context, seeking to understand the role of the school, teacher, student, and the community in general, and what can be done to improve the issue of special education every day. This is a descriptive research discussion based on recent studies that highlight the relevance of curricular adaptations, the development of assistive technologies, and the importance of continuing education for education professionals—aspects that emerge as fundamental elements for promoting inclusive and equitable education. On the other hand, current research indicates that the implementation of public policies aimed at inclusive education still faces operational and structural limitations, which reinforces the urgency of revisions and improvements that prioritize the integrality of the teaching-learning process and the active participation of all segments of society. In this sense, it can be recognized that special education is part of a multifaceted context, in which pedagogical practices are continuously reformulated based on empirical evidence and theoretical reflections that contribute to the construction of a fairer and more representative educational environment of diversity.